Konsep Penyelesaian Sengketa Pertanahan Di Indonesia Berlandaskan Prinsip Keadilan Restoratif - Febryan Alam Susatyo; Monica Belinda Oksavina; Heri Purnomo (Hukum dan Dinamika Masyarakat, 2024)
Land conflicts are often resolved through litigation considering the legal regulations that force land disputes to lead to criminal and civil justice as well as the TUN. The Land Office as the organizer of the management and registration of land rights can carry out mediation in accordance with the provisions of the Minister of Agrarian and Spatial Planning Regulation Number 21 of 2020 concerning Handling and Settlement of Land Cases. However, it is limited to certain criteria and cannot resolve problems related to land crimes and civil rights disputes. Through this research, the author proposes the concept of institutions and special rules that regulate penal mediation and civil mediation related to land conflicts in order to achieve restorative justice for the parties to the dispute. Because of this, there is a need for special institutions and special rules regarding the resolution of land conflicts through mediation in order to achieve restorative justice that is cost-effective and has a short resolution period.